Autoantibody Biomarkers for Basal Ganglia Encephalitis in Sydenham Chorea and Pediatric Autoimmune Neuropsychiatric Disorder Associated With Streptococcal Infections - Chain, Jennifer L.; Alvarez, Kathy; Mascaro-Blanco, Adita; Reim, Sean; Bentley, Rebecca; Hommer, Rebecca; Grant, Paul; Leckman, James F.; Kawikova, Ivana; Williams, Kyle; Stoner, Julie A.; Swedo, Susan E.; et al. (Frontiers in Psychiatry, 2020)
Movement, behavioral, and neuropsychiatric disorders in children have been linked to infections and a group of anti-neuronal autoantibodies, implying dopamine receptor-mediated encephalitis within the basal ganglia. The purpose of this study was to determine if anti-neuronal biomarkers, when used as a group, confirmed the acute disease in Sydenham chorea (SC) and Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcal infections (PANDAS). IgG autoantibodies against four neuronal autoantigens (tubulin, lysoganglioside GM1, and dopamine receptors D1 and D2) were detected in SC sera (N=8), sera and/or cerebrospinal fluid (CSF) from two groups of PANDAS cases (N=25 first group and N=35 second group), sera from Tourette’s Syndrome (N=18), obsessive-compulsive disorder (N=25), attention deficit hyperactivity disorder (N=18), and healthy controls (N=28) by direct enzyme-linked immunosorbent assay (ELISA). IgG specific for neuronal autoantigens was significantly elevated during the acute symptomatic phase, and the activity of calcium/calmodulin-dependent protein kinase II (CaMKII) pathway was significantly elevated in human neuronal cells. Five assays confirmed the disease in SC and in two groups of children with PANDAS. In 35 acute onset PANDAS patients, 32 sera (91.4%) were positive for one or more of the anti-neuronal autoantibodies compared with 9 of 28 healthy controls (32.1%, p<0.0001). Importantly, CSF of 32 (91.4%) PANDAS patients had one or more detectable anti-neuronal autoantibody titers and CaMKII activation. Among healthy control subjects with elevated serum autoantibody titers for individual antigens, none (0%) were positively associated with elevated positive CaMKII activation, which was a striking contrast to the sera of PANDAS subjects, who had 76-89% positive association with elevated individual autoantibody titers and positive CaMKII activity. At six months follow-up, symptoms improved for more than 80% of PANDAS subjects, and serum autoantibody titers also significantly decreased. Results reported herein and previously published studies in our laboratory suggest the antibody biomarkers may be a useful adjunct to clinical diagnosis of SC, PANDAS and related disorders and are the first known group of autoantibodies detecting dopamine receptor-mediated encephalitis in children.